Employee Empowerment and Job Satisfaction: A Systematic Literature Review - Sulistio, Ananda; Darmastuti, Ismi (LifeSciFi, 2024)
In the face of a rapidly evolving business landscape, companies need to invest more effort in strengthening their capabilities. It's essential to remember that the success and competitive edge of an organization rely on a workforce that is dedicated, highly motivated, satisfied, and innovative. Employee empowerment is regarded as a crucial practice in human1resource management due to its perceived connection with job satisfaction. This literature review synthesizes findings from research, reports, magazines, and books that relate to the investigation of the correlation between employee empowerment and job happiness. This literature demonstrates a positive association between employee empowerment and job satisfaction across many industries, including hospitality, banking, and education, at the individual, work unit, and organizational levels. In conclusion, employee empowerment can serve as a powerful tool for enhancing job satisfaction. This paper assists practitioners and other researchers in deepening their understanding of empowerment and its impact on job satisfaction.